Higher Costs for Higher Profits: A General Assessment and an Application to Environmental Regulations - Guy Meunier; Jean-Philippe Nicolaï (ETH Zurich, CER-ETH - Center of Economic Research, 2014)
We study the effect of a shock on firms' costs in a general setting by considering both perfect and imperfect competition and a general cost function. We show that, counterintuitively, firms' profits may increase with cost increases. We generalize Seade's (1985) results by considering the adaptation of firms' technological process. We find an additional effect that we call "technology effect," and which is determined by the extent to which firms' marginal and average costs differ as a result of a shock. This effect is broken down into two components: the "indirect technology effect," which is related to the elasticity of the demand slope, and the "direct technology effect," which is solely related to technology. We apply this framework to environmental regulations, which provide a good context in which to examine technological process adaptation because they push firms to use abatement technologies and to modify their production processes. We introduce an explicit abatement cost function that is sufficiently flexible to represent the various types of abatement technologies that are found in the literature: end-of-pipe technology, process-integrated technology, and cleaner production (or fuel switching). We show that end-of-pipe abatement technologies induce a positive direct technology effect, that process integrated abatement technologies induce a negative technology effect, and that cleaner production induces a null technology effect.
Keywords: L13; Q53; Q58; 330; Cournot oligopoly; Perfect competition; Cost increase; Tax on emissions; Environmental standards; Abatement technologies